2013
DOI: 10.30638/eemj.2013.089
|View full text |Cite
|
Sign up to set email alerts
|

EFFECTS OF HEAVY METALS ON Lepidium sativum GERMINATION AND GROWTH

Abstract: Basic principles for assessing phytotoxicity are the same whether the test compound is a heavy metal, herbicide, fungicide, insecticide or other toxic compounds. The difference lies not in the method of evaluation, but in the experimental program and working methodology. In this paper the phytotoxic effects of heavy metals, Cr (VI) and Cd (II) on plants germination and growth were studied. Stock solutions of the two heavy metals were prepared at a concentration of 1000 mg/L, in distilled water. Diluted working… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 45 publications
(17 citation statements)
references
References 0 publications
2
15
0
Order By: Relevance
“…In general, the decrease in phytotoxicity during composting results from the degradation of phytotoxic substances by microorganisms [51]. The present study showed that the growth of the roots of L. perenne was slightly stimulated for a compost concentration of 25%, indicating the positive impact of this material on plant growth.…”
Section: Phytotoxicity Evaluation Of Compostmentioning
confidence: 54%
“…In general, the decrease in phytotoxicity during composting results from the degradation of phytotoxic substances by microorganisms [51]. The present study showed that the growth of the roots of L. perenne was slightly stimulated for a compost concentration of 25%, indicating the positive impact of this material on plant growth.…”
Section: Phytotoxicity Evaluation Of Compostmentioning
confidence: 54%
“…Germination is one of the first stages of seed contact with a stress factor, making it a kind of sensitivity index and measure of tolerance to chemical and physical conditions of the rhizosphere [ 49 , 50 , 51 ]. During germination, the phytotoxicity of Cu and accompanying heavy metals depends on their concentration levels [ 52 , 53 , 54 ] ( Figure 1 ). Excesses cause oxidative stress by activating reactive oxygen species and inhibiting catalase activity [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…By accumulation, metal ions are retained in plant cells in a non-toxic form. Exclusion involves falling leaves to remove accumulated ions or metal complexes [7,30,61]. Plants extract from the soil and bioaccumulate the fraction of heavy metals that can be mobilized from the soil, the so-called available fraction, which confers to metals the property named metal bioavailability, i.e.…”
Section: Heavy Metals Bioavailability For Medicinal Plantsmentioning
confidence: 99%